Pharmacokinetics, Disposition, and Biotransformation of [14C]Omecamtiv Mecarbil in Healthy Male Subjects after a Single Intravenous or Oral Dose - Trivedi, Ashit; Wahlstrom, Jan; Mackowski, Mia; Dutta, Sandeep; Lee, Edward (Drug metabolism and disposition, 2021)
Omecamtiv mecarbil (OM) is a novel cardiac myosin activator that is currently in clinical development for the treatment of heart failure. The absorption and disposition of [14C]OM (60 µCi) were studied after a single intravenous infusion (35 mg over 1 hour) or oral solution dose (35 mg) in 14 healthy male subjects. Mean recovery of the administered [14C]OM dose was 85.1% and 86.5% over 336 hours for the intravenous and oral routes, respectively. After intravenous dosing, 47.8% and 37.3% of the dose was recovered in urine and feces, respectively; after oral dosing, 48.6% and 38.0% was recovered in urine and feces, respectively. Unchanged OM accounted for a minor percentage of radioactivity in urine (mean 7.7% of dose) and feces (mean 4.1% of dose) across all subjects. The major metabolites recovered in urine and feces were M3 (decarbamoylation product) and sequential metabolite M4 (lactam of M3), which accounted for means of 26.5% and 11.6% of the administered dose, respectively. The CYP4 family of enzymes was primarily responsible for the formation of M3 based on in vitro studies. Other metabolic pathways accounted for 14.9% of the administered dose. In pooled plasma, OM, M3, and M4 accounted for 83.8%, 6.0%, and 3.3% of the total [14C]OM-related materials. No other plasma metabolites constituted more than 3% of the administered dose. The bioavailability for OM solution was 93.5% after rapid and extensive absorption. This study characterized the absorption and disposition of OM, a novel small molecule being developed for the treatment of heart failure. OM was primarily cleared through metabolism by the CYP4 family through oxidative cleavage of a terminal carbamate moiety that resembles hydrolysis.